Racial Disparities in Anal Cancer Screening Among Men Living With HIV: Findings From a Clinical Cohort Study. (1st July 2020) - Gillis, Jennifer L.; Grennan, Troy; Grewal, Ramandip; Ogilvie, Gina; Gaspar, Mark; Grace, Daniel; Lofters, Aisha; Raboud, Janet M.; Saarela, Olli; Rosenes, Ron; Salit, Irving E.; Burchell, Ann N.
Abstract : Background: Our objective was to quantify the extent of anal cancer screening among men receiving HIV specialty care in Ontario, Canada, and evaluate factors associated with screening. Setting: Cross-sectional questionnaire within a multisite clinical HIV cohort. Methods: A questionnaire assessing knowledge and experience with human papillomavirus–associated diseases and their prevention was administered in 2016–2017 to 1677 men in the Ontario HIV Treatment Network Cohort Study. We used logistic regression to identify factors associated with having discussed screening with a health care provider and self-reported receipt of screening [digital anal rectal examinations (DARE); anal cytology or anoscopy]. Results reported as adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Results: Forty percent of men reported ever having had anal cytology/anoscopy, and 70% had ever had DARE. After accounting for differences in age, sexual orientation, years since HIV diagnosis, previous diagnosis with AIDS, knowing someone with human papillomavirus–associated cancer, comfort discussing anal health, education, and income, the proportion screened differed by self-identified race. Compared with white men, Asian men were less likely to have discussed screening with a health care provider (aOR = 0.48; 95% CI: 0.29 to 0.80) or to have been screened by DARE (aOR = 0.27; 95% CI: 0.17 to 0.44) or anal cytology/anoscopy (aOR = 0.51; 95% CI: 0.31 to 0.83), and African, Caribbean, or black men (aOR = 0.47; 95% CI: 0.31 to 0.70) were less likely to have had DARE. Results were consistent when restricting the analyses to gay, bisexual, and other men who have sex with men. Conclusion: Our findings highlight the potential for disparities in anal cancer screening that need to be considered when developing guidelines and screening programs to reduce the burden of anal cancer among men living with HIV and ensure health equity.